STRUKTUR LINGUISTIK BAHASA : SINTAKSIS DAN SEMANTIK - Septi Afrilia Kumala Putri; Devrianti Amanda; Silvina Noviyanti (STKIP Subang, 2025)
This research examines the linguistic structures that shape how language functions, develops, and influences human communication. The primary issue raised is the limited understanding of how syntactic and semantic components interact systematically within a language, often resulting in fragmented linguistic interpretations. The aim of this research is to provide a comprehensive and up-to-date description of linguistic structures through an empirical and theory-based approach, integrating insights from structural linguistics and contemporary linguistic models. This research uses a qualitative descriptive method utilizing data from various sources. The data is analyzed using textual analysis techniques to identify structural patterns, element functions, and meaning relationships that emerge from the use of certain syntactic forms. This approach provides space for critical observation of linguistic phenomena, questioning theoretical assumptions, and interpreting the data more contextually. The results show that changes in syntactic structure have a direct influence on shifts in meaning, while semantic context also determines the syntactic form chosen by speakers. The interaction between the two is mutually regulating and inseparable, emphasizing that meaning does not originate solely from word choice, but is the result of the relationship between grammatical structure and interpretative context. This research concludes that syntax and semantics must be analyzed in an integrated manner to understand linguistic structures comprehensively.